Evaluating youth development programs: Progress and promise. Issue 3 (2nd July 2016) - Roth, Jodie L.; Brooks-Gunn, Jeanne
ABSTRACT: Advances in theories of adolescent development and positive youth development have greatly increased our understanding of how programs and practices with adolescents can impede or enhance their development. In this article the authors reflect on the progress in research on youth development programs in the last two decades, since possibly the first review of empirical evaluations by Roth, Brooks-Gunn, Murray, and Foster (1998 ). The authors use the terms Version 1.0, 2.0, and 3.0 to refer to changes in youth development research and programs over time. They argue that advances in theory and descriptive accounts of youth development programs (Version 2.0) need to be coupled with progress in definitions of youth development programs, measurement of inputs and outputs that incorporate an understanding of programs as contexts for development, and stronger design and evaluation of programs (Version 3.0). The authors also advocate for an integration of prevention and promotion research, and for use of the term youth development rather than positive youth development.